Copper Hexacyanoferrate Formation on the Modified Silica Surface with DAB-Am-16 Dendrimer - do Carmo, Devaney R. [UNESP]; Gabriel, Suelino [UNESP]; Bicalho, Urquisa O. [UNESP]; Picon, Carlos A. [UNESP]; Paim, Leonardo L. (Wiley-v C H Verlag Gmbh, 2011)
The third generation (G-3) polypropylenimine hexadecaamine dendrimer (DAB-Am-16) was grafted onto the silica gel surface. The modified silica interacts easily with Cu(2+) and then with potassium ferrocyanide to form copper hexacyanoferrate. The modified silica was characterized by the following techniques: Nuclear Magnetic Resonance (NMR), FTIR spectroscopy, Energy Dispersive X-ray (EDX) and Cyclic Voltammetry. The modified silica containing copper hexacyanoferrate (CuHCFSD) was tested for a voltammetric determination of nitrite using a modified graphite paste electrode.
Keywords: composites; copper hexacyanoferrate; polypropylenimine hexadecaamine dendrimer; silica gel; voltammetry cyclic